MicroRNA-21: An Emerging Player in Bone Diseases - Chen, Chen; Liu, Ya-Mei; Fu, Bin-Lan; Xu, Liang-Liang; Wang, Bin (Frontiers in Pharmacology, 2021)
MicroRNAs (MiRNAs) are small endogenous non-coding RNAs that bind to the 3′-untranslated region of target genes and promote their degradation or inhibit translation, thereby regulating gene expression. MiRNAs are ubiquitous in biology and are involved in many biological processes, playing an important role in a variety of physiological and pathological processes. MiRNA-21 (miR-21) is one of them. In recent years, miR-21 has received a lot of attention from researchers as an emerging player in orthopedic diseases. MiR-21 is closely associated with the occurrence, development, treatment, and prevention of orthopedic diseases through a variety of mechanisms. This review summarizes its effects on osteoblasts, osteoclasts and their relationship with osteoporosis, fracture, osteoarthritis (OA), osteonecrosis, providing a new way of thinking for the diagnosis, treatment and prevention of these bone diseases.